Immunopharmacogenomics: Mechanisms of HLA‐Associated Drug Reactions. Issue 3 (17th July 2021) - Deshpande, Pooja; Hertzman, Rebecca J.; Palubinsky, Amy M.; Giles, Jason B.; Karnes, Jason H.; Gibson, Andrew; Phillips, Elizabeth J.
Abstract : The human leukocyte antigen (HLA) system is the most polymorphic in the human genome that has been associated with protection and predisposition to a broad array of infectious, autoimmune, and malignant diseases. More recently over the last two decades, HLA class I alleles have been strongly associated with T‐cell‐mediated drug hypersensitivity reactions. In the case of abacavir hypersensitivity and HLA‐B*57:01, the 100% negative predictive value and low number needed to test to prevent a single case has led to a durable and effective global preprescription screening strategy. However, HLA associations are still undefined for most drugs clinically associated with different delayed drug hypersensitivity phenotypes, and an HLA association relevant to one population is not generalizable across ethnicities. Furthermore, while a specific risk HLA allele is necessary for drug‐induced T‐cell activation, it is not sufficient. The low and incomplete positive predictive value has hindered efforts at clinical implementation for many drugs but has provided the impetus to understand the mechanisms of HLA class I restricted T‐cell‐mediated drug hypersensitivity reactions. Current research has focused on defining the contribution of additional elements of the adaptive immune response and other genetic and ecologic risk factors that contribute to drug hypersensitivity risk. In this review we focus on new insights into immunological, pharmacological, and genetic mechanisms underpinning HLA‐associated drug reactions and the implications for future translation into clinical care.